La Declaración Judicial de Privación de la Patria Potestad y su incidencia frente al Principio Constitucional del Desarrollo Integral del menor, en la Unida Judicial de la familia, mujer , niñez y adolescencia con sede en el cantón Riobamba en el periodo Enero - Junio 2015. - Gutierréz Guamán, Geovana Nataly (2016)
In Ecuador there is abundant legislation which aims to insure the rights of children and adolescents and to guarantee their development, because sometimes parents act carelessly towards their children to the point that children are assaulted by them producing a serious physical or psychological injury, so the state intervenes within the family as a guarantor of fundamental right of children and adolescents. So, that is why in many cases it limits or deprives of guardianship rights to the parents. For the reasons above, a procedure to limit or deprive the parents of their rights over their children has been established in the respective law when parents put under danger or risk to their children, so they would lose guardianship over the progenies. Causes will be studied during this research. Gravity of the causes and guardianship right must be established by a certain judicial process. Finally, it is important to mention that the Constitution of the Republic of Ecuador looks after the interests of children and adolescents, and physical and integral development. So, it becomes indispensable to safeguard this helpless creature.